FINANCIAL AND ECONOMIC SAFETY OF ECONOMIC AGENTS - V. I. Avdiysky; V. M. Bezdenezhnyh; V. E. Liechtenstein; G. V. Ross; K. I. Solodovnikova (Финансы: теория и практика, 2017)
The article discusses the sources of error of the indicators and tests of the security of economic agents, the mechanisms, which make them inadequate are identifi ed. A new scientifi c and methodological approach to creating the information systems for identify security threats of economic agents, which based on the equilibrium theory of random processes is proposed. In particular, we performed a review of the literature, which allows to draw the following main conclusions: fi rst, there is no shortage in the number and variety of indicators and tests, no diffi culties in the development of new, able to take into account the specifi c characteristics of each economic agent in specifi c circumstances; secondly, all the indicators and tests (at least the ones that we have found in the press) do not take into account the impact on the emergence of threats to fi nancial bubbles, money laundering, fi nancial terrorism, systematic or intentional distortion of statistical reporting, the use of virtual currencies and online games to move the capital; third, all indicators and tests ignore the infl uence of psychology on the behavior of economic agents, in particular, the real and subjective risks and methodical features of the calculation of economic indicators. We propose in this article a new methodological apparatus, which allows to consider all the sources of threats and reduce the error of the indicators in the form of intervals of uncertainty, and in the form of offset of the indicators.